POLA KONSUMSI RUMAH TANGGA MASYARAKAT PENERIMA PROGRAM BANTUAN SOSIAL - Rahmayunizar, Anisya; Warneri, Warneri; Budiman, Jumardi (Universitas Tanjungpura, 2024)
Social assistance has an important role in supporting the welfare of people's lives because providing social assistance can overcome social and economic inequality. Therefore, the aim of this research is to determine the effects that occur from the consumption patterns of people who receive social assistance. In this research, the approach used is a qualitative method with an interactive form of inquiry. Results of interviews and observations with 6 informants consisting of the community in RW 14 Sungai Jawi Village. Data collection was carried out using closed interview methods, and observation as well as some documentation that was relevant to this research. Based on the results of research that has been carried out, it is known that people's consumption patterns are very dependent on the income they earn, so that they can spend this income on various needs. From the research results, it is also known that the consumption patterns carried out by the community in RW 14 Sungai Jawi Village are irregular or irregular, this is based on the fact that most of the poor people in Sungai Jawi Village do not have a fixed income. With the Family Hope Program (PKH) Social Assistance, the positive impact felt by the community is that it can ease the burden of community expenses and can help families who are PKH participants to pay for school children at the elementary, middle and high school levels.